The Role of Antiangiogenic Drugs in the Treatment of Diabetic Macular Edema - o’g’li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2023)
The article presents the characteristics of the first antiangiogenic drug registered for the treatment of diabetic macular edema, ranibizumab, as well as the new long-acting drug brolucizumab.